Design Thinking of Indonesia's Post-Jokowi Education Policy - Hastangka, Hastangka (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Education during Jokowi's administration was rarely a topic of discussion. In the 2-year document Jokowi-JK Real Work shows that education is less of a major concern in the Jokowi administration's policy agenda. The three main focuses of the government's policy agenda emphasize infrastructure, human development, and economic deregulation policies. Education is only limited to the mention of increased access and infrastructure of education, and the education index which increased (0.82) from 2014 to 2015. A number of education policy products such as the smart Indonesia card, KIP Kuliah have become a legacy in the Jokowi administration from 2014 to 2024. However, a number of educational problems and challenges have not been fully answered during Jokowi's leadership. This happens because there is no adequate design thinking in overcoming education problems in Indonesia. The purpose of the research is to uncover and analyze the fundamental problems of education and propose the formulation of design thinking of Indonesian education policy after Jokowi. The method used in this study uses a qualitative approach. Data is obtained through literature studies of government policy documents in the field of education, books, scientific journal articles. Data analysis uses interpretive approaches, semiotics, critical discourse analysis, and design thinking. The results of this study show that if we look at post-reform education policy, design thinking education policy has not touched on the fundamental education system, the substance of education, and the culture and ecosystem of education. Therefore, the design thinking proposed after the Jokowi administration is directed to build and strengthen three aspects, namely regulation, governance, and education human resources.